2021
DOI: 10.3390/plants10071304
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Sulphur Fertilisation for Marketable Yields of Cabbage (Brassica oleracea L. var. Capitata), Leaf Nitrate and Glucosinolates and Nitrogen Losses Studied in a Field Experiment in Central Slovenia

Abstract: A field trial of white cabbage (Brassica oleracea var. Capitata L.) was carried out under the humid temperate climate conditions in Central Slovenia to investigate the effects of calcium ammonium nitrate (0, 180 and 240 kg N ha−1) and gypsum (0 and 40 kg S ha−1) fertilisation on yield, yield quality (nitrate, glucosinolate levels and glucosinolate profile) and nitrogen use efficiency. The highest marketable yield, dry matter yield and nitrogen uptake were obtained at the highest nitrogen fertilisation rate whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…In agreement with our results, several studies showed that sulfur fertilization may increase NUE [ 75 , 76 , 77 ]. As sulfur is an essential constituent of enzymes involved in nitrogen metabolism [ 78 ], its deficiency may lead to ineffective utilization of the nitrogen content in plant [ 79 , 80 ].…”
Section: Resultssupporting
confidence: 93%
“…In agreement with our results, several studies showed that sulfur fertilization may increase NUE [ 75 , 76 , 77 ]. As sulfur is an essential constituent of enzymes involved in nitrogen metabolism [ 78 ], its deficiency may lead to ineffective utilization of the nitrogen content in plant [ 79 , 80 ].…”
Section: Resultssupporting
confidence: 93%
“…In general, the lowest marketable yield might be recorded from any of the control treatments having no nutrients applied [ 53 ]. Even the minimum yield per hectare could be attained from any of the control treatments in cabbage production [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cabbage yields typically range from 14.2 t ha −1 to 139.2 t ha −1 . This wide variation in yield is mainly attributed to the specific hybrid cultivated and the applied management practices, such as plant spacing, growing season and fertilization [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%